The effect of COVID-19 lockdown on ball possession performance in Spanish professional soccer leagues - Lobo-Trivino, D.; Ponce-Bordon, J. C.; Díaz-García, J.; López Del Campo, R.; Doncel, A.; Fernández-Navarro, J.; García-Calvo, T. (International Journal of Performance Analysis in Sport, 2024)
This research analysed the influence of lockdown and interruption of competitions due to COVID-19 on different ball possession-related variables. Also, match location and the differences between divisions were considering between the pre- and post-lockdown. A total of 144,689 records from 842 soccer matches during the 2019/20 season of the First (n = 380) and Second Spanish Division (n = 462) were collected. Match data were collected using the ChryonHego video-tracking system. Pre-lockdown (1st-27th matchday in First Division and 1st-31st matchday in Second Spanish Division) and post-lockdown periods (28th-38th matchday in First Division and 32nd-42nd matchday in Second Spanish Division) were compared. The match location contextual-related variable was also considered for the analysis. Linear mixed models showed that the number of outplayed players by ball possession (3.1%), successful passes (17.5%) and total passes (18.9%) increased during the post-lockdown period (p < .001). In addition, match location and league significantly influenced the successful and total passes in all situations (p < .001), increasing in the post-lockdown period. In conclusion, the lockdown period has led changes in the ball possession of the soccer teams. These results help to understand the impact that a particular and unusual situation as the interruption of the league due to COVID-19 lockdown had on the performance of professional soccer teams.